Competitive analysis of k-server variants and metrical task systems - Coester, C (2019)
In the online k-server problem, an algorithm controls k mobile servers in a metric space. One by one, requests arrive at points of the space, and the algorithm must serve each request by selecting a server to visit it. The goal is to minimize the total distance traveled by all servers. In the framework of competitive analysis, we study two variants of the k-server problem, the infinite server problem and the k-taxi problem, and the more general metrical task systems problem.